Characterization and performance of agronomic characters of soybean genotypes resistant to pod shattering - AYDA KRISNAWATI; M. MUCHLISH ADIE (Biodiversitas Journal of Biological Diversity, 2017)
Krisnawati A, Adie MM. 2017. Characterization and performance of agronomic characters of soybean genotypes resistant to pod shattering. Biodiversitas 18: 1158-1164. Pod shattering is one of the major obstacles of soybean cultivation in Indonesia’s tropical climate. A total of 24 soybean genotypes, including Anjasmoro (check variety for pod-shatter resistant), Argomulyo and Grobogan (susceptible to pod shattering). The field experiment was conducted in Banyuwangi (East Java, Indonesia) during the dry season II 2016. The experimental design was randomized block, consisted of 24 soybean genotypes as sample trait with four replications. Pods from six random plants at physiological maturity (R8) were detached for pod shattering evaluation. The pod shattering evaluation was conducted in Laboratory of Plant Breeding, Indonesian Legumes and Tuber Crops Research Institutes (Malang, Indonesia) by using oven method and ambient temperature method. The classification of shattering resistance was according to Bailey et al. (1997) and Mohammed (2010), i.e. resistant (0-10% shattered pods), intermediate (11-70 % shattered pods) and susceptible (71-100% shattered pods). The average shattered pods of 24 genotypes by oven method reached 42.67%, higher than those of ambient method (21.81%). Six soybean genotypes showed consistently resistant to pod shattering based on oven as well as ambient method. Pods position at lower part was more susceptible to pod shattering than those at middle and upper part. The limit of pod shattering was ranging from two to 38 days. Genotype of G511H/Anjs/Anjs-1-2 which characterized by pod shatter resistant, produced high yield, and large seed size, was potentially developed at the tropical area, such as Indonesia.